Self Efficacy dan Gaya Hidup Pasien Hipertensi - Amila Amila; Janno Sinaga; Evarina Sembiring (Jurnal Kesehatan, 2018)
Hypertension is one of the major cardiovascular diseases worldwide. Self-efficacy, a widely used psychosocial concept, is associated with the ability to manage chronic disease. The purposes of this study were to identify the correlation between self-efficacy with lifestyle on hypertension patients. The data obtained were analyzed by correlational analytic with a cross-sectional approach. The sample of this study was recruited with total sampling as much as 130 people. Data were collected with a questionnaire toward the hypertension patients who came to Mutiara Homecare Medan. The data were analyzed by Spearman correlation with significance α<0.05. The study showed that self-efficacy of patients with hypertension was majorly high(96,9%), and lifestyle was a majorly healthy lifestyle (96,2%). There was a significant correlation between self-efficacy with lifestyle on hypertension patients (r=0.8.91; p<0.05). Nurses can increase self-efficacy of hypertension patients by providing support and motivation to improve a healthy lifestyle to prevent further complications.